Health education and global health: Practices, applications, and future research - Daliya S Rizvi (Wolters Kluwer Medknow Publications, 2022)
Health education is a crucial consideration in the healthcare system and has the potential to improve global health. Recently, researchers have expressed interest in streamlining health education, utilizing digital tools and flexible curriculums to make it more accessible, and expanding beyond disease and substance abuse prevention. They have also expressed interest in promoting global health through health and safety promotion programs. Amidst the COVID-19 pandemic, climate change, the refugee crisis, and overpopulation, healthcare crises are erupting all over the world. A lack of health education has and will continue to have a profound impact on community healthcare indicators, particularly in low-income nations. Current priorities within the health education sector include digitization, equity, and infectious disease prevention. Studies and data from university journals and other academic databases were analyzed in a literature review. Health education programs have a significant positive impact on attitudes and behaviors regarding global health. Improving upon these programs by digitizing them and expanding upon the scope of health education will help ensure that such interventions and programs make a significant difference.